Discovery of a potent FKBP38 agonist that ameliorates HFD-induced hyperlipidemia via mTOR/P70S6K/SREBPs pathway - Ping-Ting Xiao (Elsevier, 2021)
The mammalian target of rapamycin (mTOR)-sterol regulatory element-binding proteins (SREBPs) signaling promotes lipogenesis. However, mTOR inhibitors also displayed a significant side effect of hyperlipidemia. Thus, it is essential to develop mTOR-specific inhibitors to inhibit lipogenesis. Here, we screened the endogenous inhibitors of mTOR, and identified that FKBP38 as a vital regulator of lipid metabolism. FKBP38 decreased the lipid content in vitro and in vivo via suppression of the mTOR/P70S6K/SREBPs pathway. 3,5,6,7,8,3ʹ,4ʹ-Heptamethoxyflavone (HMF), a citrus flavonoid, was found to target FKBP38 to suppress the mTOR/P70S6K/SREBPs pathway, reduce lipid level, and potently ameliorate hyperlipidemia and insulin resistance in high fat diet (HFD)-fed mice. Our findings suggest that pharmacological intervention by targeting FKBP38 to suppress mTOR/P70S6K/SREBPs pathway is a potential therapeutic strategy for hyperlipidemia, and HMF could be a leading compound for development of anti-hyperlipidemia drugs.